2022
DOI: 10.1108/cg-09-2021-0331
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable governance and climate-change disclosure in European banking: the role of the corporate social responsibility committee

Abstract: Purpose The purposes of this paper are: firstly, to assess the disclosure related to climate change (CC) by major European banks to understand if the banks have grasped the most substantive aspects of the Task Force on Climate-related Financial Disclosures (TCFD) recommendations and secondly, to evaluate the contribution of a non-traditional committee (i.e. corporate social responsibility (CSR) committee) to TCFD-compliant disclosure. Design/methodology/approach Using content analysis and ordinary least squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
48
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 77 publications
5
48
4
1
Order By: Relevance
“…category. In contrast to our analysis,Cosma et al (2022) saw the greatest weaknesses in climate reporting in the area of Governance.They concluded that while banks have started to assess the business and risk impacts of climate change, they have not yet completed the upstream and downstream processes on associated roles and responsibilities. However, our further analysis shows that significant improvements in reporting quality were visible in the area of Governance, particularly from 2019 to 2020.…”
contrasting
confidence: 97%
See 3 more Smart Citations
“…category. In contrast to our analysis,Cosma et al (2022) saw the greatest weaknesses in climate reporting in the area of Governance.They concluded that while banks have started to assess the business and risk impacts of climate change, they have not yet completed the upstream and downstream processes on associated roles and responsibilities. However, our further analysis shows that significant improvements in reporting quality were visible in the area of Governance, particularly from 2019 to 2020.…”
contrasting
confidence: 97%
“…This should include information on the existence of incentive systems for members of the administrative, management, and supervisory bodies that are linked to sustainability aspects. These incentive systems are therefore not necessarily limited to pure compensation systems.UnlikeCosma et al (2022), we see the largest reporting gaps in the core category of Strategy. In this context, we observed that although the majority of banks have already identified climate-related risks and opportunities, a majority of them do not differentiate between short-, medium-, or long-term climate-related impacts.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, researchers should play an important role among non-state actors needed to resist this global problem. The prestige of the research provided by the scientific community will subsequently be reflected in the approval of public polices [8] and the improvement in voluntary social and business actions [9] that will enable net zero emissions to be achieved by 2050.…”
mentioning
confidence: 99%